Chimeric camel/human heavy-chain antibodies protect against MERS-CoV infection - Stalin Raj, V. (Sci Adv, 2018)
Middle East respiratory syndrome coronavirus (MERS-CoV) continues to cause outbreaks in humans as a result of spillover events from dromedaries. In contrast to humans, MERS-CoV–exposed dromedaries develop only very mild infections and exceptionally potent virus-neutralizing antibody responses. These strong antibody responses may be caused by affinity maturation as a result of repeated exposure to the virus or by the fact that dromedaries—apart from conventional antibodies—have relatively unique, heavy chain–only antibodies (HCAbs). These HCAbs are devoid of light chains and have long complementarity-determining regions with unique epitope binding properties, allowing them to recognize and bind with high affinity to epitopes not recognized by conventional antibodies. Through direct cloning and expression of the variable heavy chains (VHHs) of HCAbs from the bone marrow of MERS-CoV–infected dromedaries, we identified several MERS-CoV–specific VHHs or nanobodies. In vitro, these VHHs efficiently blocked virus entry at picomolar concentrations. The selected VHHs bind with exceptionally high affinity to the receptor binding domain of the viral spike protein. Furthermore, camel/human chimeric HCAbs—composed of the camel VHH linked to a human Fc domain lacking the CH1 exon—had an extended half-life in the serum and protected mice against a lethal MERS-CoV challenge. HCAbs represent a promising alternative strategy to develop novel interventions not only for MERS-CoV but also for other emerging pathogens.